Medieval Costume and How to Make It - Hartley, Dorothy (Angelico Press, 2016)
Clear and accurate in its guidance, Medieval Costume and How to Make It portrays the clothing of the 12th through the 15th centuries according to the wearer's social class, with chapters divided to cover individual professions. So in addition to royal garments, here are the clothes of clerics, doctors, merchants, musicians, knights, artisans, farmers, and laborers--all with much useful historical information, and richly illustrated with images from tapestries and illuminated manuscripts of the period as well as drawings and diagrams. Helpful advice covers choosing fabrics; placement of seams; draping and folding garments; how to walk, dance, and climb stairs in flowing attire; and even the best methods of storage. There are also many interesting details of accessories found in different professions and situations. Students of medieval costume design, tailors, community theater and reenactment groups--all will welcome this sumptuous guidebook to medieval costume.